Myeloid cell‐based delivery of IFN‐γ reprograms the leukemia microenvironment and induces anti‐tumoral immune responses. Issue 10 (30th August 2021) - Mucci, Adele; Antonarelli, Gabriele; Caserta, Carolina; Vittoria, Francesco Maria; Desantis, Giacomo; Pagani, Riccardo; Greco, Beatrice; Casucci, Monica; Escobar, Giulia; Passerini, Laura; Lachmann, Nico; Sanvito, Francesca; et al.
Abstract: The immunosuppressive microenvironment surrounding tumor cells represents a key cause of treatment failure. Therefore, immunotherapies aimed at reprogramming the immune system have largely spread in the past years. We employed gene transfer into hematopoietic stem and progenitor cells to selectively express anti‐tumoral cytokines in tumor‐infiltrating monocytes/macrophages. We show that interferon‐γ (IFN‐γ) reduced tumor progression in mouse models of B‐cell acute lymphoblastic leukemia (B‐ALL) and colorectal carcinoma (MC38). Its activity depended on the immune system's capacity to respond to IFN‐γ and drove the counter‐selection of leukemia cells expressing surrogate antigens. Gene‐based IFN‐γ delivery induced antigen presentation in the myeloid compartment and on leukemia cells, leading to a wave of T cell recruitment and activation, with enhanced clonal expansion of cytotoxic CD8 + T lymphocytes. The activity of IFN‐γ was further enhanced by either co‐delivery of tumor necrosis factor‐α (TNF‐α) or by drugs blocking immunosuppressive escape pathways, with the potential to obtain durable responses. SYNOPSIS: IFN‐γ gene therapy is safe and reduces tumor progression in mouse models of B‐cell acute lymphoblastic leukemia and colorectal carcinoma. Its effects are immune‐mediated through antigen‐presentation and reprogramming of the tumor microenvironment. IFN‐γ antitumor effects are driven by immune activation through antigen presentation, clonal T cell expansion, and TME reprogramming. Combining IFN‐γ gene therapy with other immunotherapies leads to enhanced and prolonged anti‐tumoral activity. Abstract : IFN‐γ gene therapy is safe and reduces tumor progression in mouse models of B‐cell acute lymphoblastic leukemia and colorectal carcinoma. Its effects are immune‐mediated through antigen‐presentation and reprogramming of the tumor microenvironment.